2021
DOI: 10.3389/fneur.2021.625334
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic Intensities of Light at Night: A Review of the Potent Effects of Very Dim Light on Circadian Responses and Considerations for Translational Research

Abstract: In this review, we discuss the remarkable potency and potential applications of a form of light that is often overlooked in a circadian context: naturalistic levels of dim light at night (nLAN), equivalent to intensities produced by the moon and stars. It is often assumed that such low levels of light do not produce circadian responses typically associated with brighter light levels. A solid understanding of the impacts of very low light levels is complicated further by the broad use of the somewhat ambiguous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 178 publications
(252 reference statements)
1
22
0
Order By: Relevance
“…6 for an aerial view of the facility). Instead of "dark" controls, the controls were exposed to natural light (34). This ensured perfect flexibility in the allocation of treatments to the experimental units and precluded any unintended systematic influences of the illumination system (e.g.…”
Section: Practical Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…6 for an aerial view of the facility). Instead of "dark" controls, the controls were exposed to natural light (34). This ensured perfect flexibility in the allocation of treatments to the experimental units and precluded any unintended systematic influences of the illumination system (e.g.…”
Section: Practical Implementationmentioning
confidence: 99%
“…Consequently, experimental test sites have been established to assess consequences of direct ALAN exposures, mainly street lighting (31,32,33). Experiments on skyglow, however, are challenging because the spatial light field of the diffuse uniform illumination of skyglow is difficult to emulate, lighting structures shade natural light, and dark experimental control units can be accidentally illuminated (34).…”
Section: Introductionmentioning
confidence: 99%
“…To enable a clear interpretation of the results and “future-proof” 46 research efforts requires adequate documentation of study conditions going well beyond current standard practice. A recent examination of 71 studies on the biological effects of light revealed that 55% (39/71) did not report any information about spectrum, and an overwhelming majority (87%; 62/71) only reported light levels in lux 47 , representing a quantity weighting L and M cone activity, which is inappropriate given the converging evidence of the dominant role of melanopsin 27 29 , 48 . Furthermore, there is large variability in what is considered “dim light”, with light levels called “dim” in practice spanning almost two log units 47 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent examination of 71 studies on the biological effects of light revealed that 55% (39/71) did not report any information about spectrum, and an overwhelming majority (87%; 62/71) only reported light levels in lux 47 , representing a quantity weighting L and M cone activity, which is inappropriate given the converging evidence of the dominant role of melanopsin 27 29 , 48 . Furthermore, there is large variability in what is considered “dim light”, with light levels called “dim” in practice spanning almost two log units 47 . Since a key biomarker for circadian phase, the “dim light melatonin onset” (DLMO) 49 , 50 , hinges upon data collection in dim lighting conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, experimental test sites have been established to assess consequences of direct ALAN exposures, mainly street lighting 31 – 33 . Experiments on skyglow, however, are challenging because the spatial light field of the diffuse uniform illumination of skyglow is difficult to emulate, lighting structures shade natural light, and dark experimental control units can be accidentally illuminated 34 . One possible approach is to document ecological responses before and after switching off skyglow sources at the whole-village or city scale.…”
Section: Introductionmentioning
confidence: 99%